2022
DOI: 10.3390/nu14234991
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Omega-3 and Omega-6 Derived Oxylipins Are Associated with Fecal Microbiota Composition in Young Adults

Abstract: Pre-clinical studies suggest that circulating oxylipins, i.e., the oxidation products of polyunsaturated fatty acids (PUFAs), modulate gut microbiota composition in mice, but there is no information available in humans. Therefore, this study aimed to investigate the relationship between omega-3 and omega-6 derived oxylipins plasma levels and fecal microbiota composition in a cohort of young adults. 80 young adults (74% women; 21.9 ± 2.2 years old) were included in this cross-sectional study. Plasma levels of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…If true, the change in gut microbiota diversity may amplify the generation of gut-derived phenolics linked to increased blueberry intake over time. The positive correlations between concentrations of urine blueberry gut-derived phenolics and post-exercise plasma DHA-LOX HDoHEs and SPM intermediates support this potential relationship [26,27]. These correlation data were significant only at the immediate postexercise time point and explained only a small proportion of the variance.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…If true, the change in gut microbiota diversity may amplify the generation of gut-derived phenolics linked to increased blueberry intake over time. The positive correlations between concentrations of urine blueberry gut-derived phenolics and post-exercise plasma DHA-LOX HDoHEs and SPM intermediates support this potential relationship [26,27]. These correlation data were significant only at the immediate postexercise time point and explained only a small proportion of the variance.…”
Section: Discussionmentioning
confidence: 61%
“…Underlying mechanisms are still being explored but limited data suggest that increases in gut-derived phenolics and changes in the gut microbiome from added polyphenol intake may influence oxylipin production through effects on related enzyme systems including cPLA2, CYP, sEH, LOX, and COX [26][27][28]. Human data are lacking but the available data suggest modulations of the gut microbiota with blueberry and anthocyanin ingestion [28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous research has demonstrated that GM can lower Omega-3 PUFA levels by promoting the conversion of PUFA precursors like alpha-linolenic acid (ALA) and linoleic acid (LA) into conjugated linoleic acid (CLA) and hydrogenating conjugated alpha-linolenic acid (CALA) into saturated fatty acids, such as stearic acid ( Jenkins et al, 2008 ; Shama and Liu, 2020 ). Xu H. et al research revealed that specific gut bacteria can increase the levels of omega-3 oxysphospholipids, derived from omega-3 PUFA, with potential benefits for both systemic and gut health ( Xu et al, 2022 ). Another earlier study has provided insights into how the GM produces enzymes involved in pathways related to fatty acid metabolism, thus enabling the conversion of PUFA in the gastrointestinal tract ( Kishino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize that the so-called dysbiosis involving genus Acidaminococcus associates with CVS throughout the in ammatory mediators in the vessel wall and could corroborate the in ammatory theory of CVS. Indeed, Acidaminococcus was negatively correlated with plasma levels of omega-6-derived oxylipins 39 , and importantly, oxylipins such as 20-hydroxyeicosatetraenoic acid were reported to be involved in cerebral vasospasm following aSAH 40 -see Fig. 5.…”
Section: Acidaminococcus and In Ammatory Fundamentals Of Cvsmentioning
confidence: 99%